2021
DOI: 10.21608/javs.2021.80220.1085
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Wheat Germ Oil Against Adverse Effect of Deltamethrin on Reproductive Aspects of Male Albino Rats

Abstract: Deltamethrin (DLM) is a synthetic pyrethroid type-II known to cause many adverse effects in experimental animals such as endocrine disruption, reproductive toxicity, and negative impact on gametogenesis. The present study was conducted to evaluate the protective role of wheat germ oil against reproductive toxicity induced by Deltamethrin (DLM) in male albino rats through evaluation of semen picture, measuring the testosterone levels, DNA fragmentation percentage and pathologic changes of the testes. Thirty mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…This study reports WGO as a protective agent against liver and kidney damage in mice. Previous studies showed the protective effects of WGO against streptozotocin, deltamethrin, and chlorpyriphos [45,46]. To the best of our knowledge, no study reported that the supplementation of WGO might be a promising strategy for managing or decreasing the side effects of chemotherapeutic drugs such as olmutinib and TAA.…”
Section: Discussionmentioning
confidence: 98%
“…This study reports WGO as a protective agent against liver and kidney damage in mice. Previous studies showed the protective effects of WGO against streptozotocin, deltamethrin, and chlorpyriphos [45,46]. To the best of our knowledge, no study reported that the supplementation of WGO might be a promising strategy for managing or decreasing the side effects of chemotherapeutic drugs such as olmutinib and TAA.…”
Section: Discussionmentioning
confidence: 98%
“…The WG oil had its powerful effect in rising the reproductive traits of Sinaii gabali rabbit bucks especially on conception rate%, the gestation length of does inseminated with semen of rabbit fed wheat germ oil, also the litter size at birth and weaning, the litter weight at birth and weaning, and decreasing the mortality rate at weaning [15]. The WG oil can mitigate the adverse effect of pollutants on male fertility, and leads to improvement of male reproductive performance [16]. Donoghue and Walker-Simmons [17] reported that the supply of 10% wheat protein extract to semen stored 24 h at 5°C enhanced fertility and hatchability of eggs over semen stored in diluent alone (P<0.05).…”
Section: Introductionmentioning
confidence: 99%